Cultural Diversity and Marketing Transactions: Are Market Integration, Large Community Size, And World Religions Necessary for Fairness in Ephemeral Exchanges? - Woodside, Arch; Zhang, Mann (John Wiley & Sons, Inc., 2013)
The study here applies qualitative comparative analysis (QCA) in an examination of data from 15 societies varying in their degree of market integration (MI) and participation in world religions (WRs); the data are available in Henrich et al. (2010b). The findings here provide a more nuanced coverage of the influences of cultural causal recipes on fairness and punishment in exchanges with strangers than “net effect” explanations. The coverage here explains how acts of fairness and punishment are contingent on several alternative paths including both low as well as high levels of MI and WR. Contrary to conclusions by Henrich et al. (2010a), depending on additional ingredients in cultural recipes, a society does not need to achieve MI and adoption of a WR to be fair and punish unfairness.